Patterns of PD-L1 expression and CD8 T cell infiltration in gastric adenocarcinomas and associated immune stroma. Issue 5 (22nd January 2016) - Thompson, Elizabeth D; Zahurak, Marianna; Murphy, Adrian; Cornish, Toby; Cuka, Nathan; Abdelfatah, Eihab; Yang, Stephen; Duncan, Mark; Ahuja, Nita; Taube, Janis M; Anders, Robert A; Kelly, Ronan J
Abstract : Objective: Recent data supports a significant role for immune checkpoint inhibitors in the treatment of solid tumours. Here, we evaluate gastric and gastro-oesophageal junction (G/GEJ) adenocarcinomas for their expression of programmed death-ligand 1 (PD-L1), infiltration by CD8+ T cells and the relationship of both factors to patient survival. Design: Thirty-four resections of primary invasive G/GEJ were stained by immunohistochemistry for PD-L1 and CD8 and by DNA in situ hybridisation for Epstein–Barr virus (EBV). CD8+ T cell densities both within tumours and at the tumour–stromal interface were analysed using whole slide digital imaging. Patient survival was evaluated according to PD-L1 status and CD8 density. Results: 12% of resections showed tumour cell membranous PD-L1 expression and 44% showed expression within the immune stroma. Two cases (6%) were EBV positive, with one showing membranous PD-L1 positivity. Increasing CD8+ densities both within tumours and immune stroma was associated with increasing percentage of tumour (p=0.027) and stromal (p=0.005) PD-L1 expression. Both tumour and immune stromal PD-L1 expression and high intratumoral or stromal CD8+ T cell density (>500/mm 2 ) were associated with worse progression-free survival (PFS) and overall survival (OS). Conclusions: PD-L1 is expressed on both tumour cells and in the immune stroma across all stages and histologies of G/GEJ. Surprisingly, we demonstrate that increasing CD8 infiltration is correlated with impaired PFS and OS. Patients with higher CD8+ T cell densities also have higher PD-L1 expression, indicating an adaptive immune resistance mechanism may be occurring. Further characterisation of the G/GEJ immune microenvironment may highlight targets for immune-based therapy.